LncRNA SOX1‐OT V1 acts as a decoy of HDAC10 to promote SOX1‐dependent hESC neuronal differentiation. (20th December 2021) - Xi, Jiajie; Xu, Yanxin; Guo, Zhenming; Li, Jianguo; Wu, Yukang; Sun, Qiaoyi; Wang, Yuxi; Chen, Mengxia; Zhu, Songcheng; Bian, Shan; Kang, Jiuhong
Abstract: Long noncoding RNAs (lncRNAs) are abundantly expressed in the nervous system, but their regulatory roles in neuronal differentiation are poorly understood. Using a human embryonic stem cell (hESC)‐based 2D neural differentiation approach and a 3D cerebral organoid system, we show that SOX1‐OT variant 1 ( SOX1‐OT V1), a SOX1 overlapping noncoding RNA, plays essential roles in both dorsal cortical neuron differentiation and ventral GABAergic neuron differentiation by facilitating SOX1 expression. SOX1‐OT V1 physically interacts with HDAC10 through its 5' region, acts as a decoy to block HDAC10 binding to the SOX1 promoter, and thus maintains histone acetylation levels at the SOX1 promoter. SOX1 in turn activates ASCL1 expression and promotes neuronal differentiation. Taken together, we identify a SOX1‐OT V1/HDAC10‐SOX1‐ASCL1 axis, which promotes neurogenesis, highlighting a role for lncRNAs in hESC neuronal differentiation. Synopsis: SOX1‐OT V1 interacts with HDAC10 and blocks its binding to the SOX1 promoter, maintaining histone acetylation levels at the promoter to facilitate SOX1 expression. SOX1 in turn activates ASCL1 expression to promote dorsal cortical neuron and ventral GABAergic neuron differentiation. SOX1‐OT V1 promotes histone acetylation at the SOX1 promoter. SOX1‐OT V1 acts as a decoy of HDAC10 to block HDAC10 binding to the SOX1 promoter SOX1 directly activates ASCL1 to promote hESC neuronal differentiation Abstract : SOX1‐OT V1 interacts with HDAC10 and blocks its binding to the SOX1 promoter, maintaining histone acetylation levels at the promoter to facilitate SOX1 expression. SOX1 in turn activates ASCL1 expression to promote dorsal cortical neuron and ventral GABAergic neuron differentiation.